Opening Access to Research. (August 2015) - Armstrong, Mark
<x xml:space="preserve">Abstract</x> Many scholarly journals charge high prices to libraries, exclude the wider public altogether, and generate excessive profits. Open access regulation can mitigate these problems when authors are required to publish in journals which offer free and immediate access by readers, or make freely available a substitute to the published article. The former policy is likely to lead to publication fees, making authors less inclined to publish and less willing to publish in selective journals. The latter policy makes available only an inferior version of the published article but may be consistent with authors publishing for free.